BALANCING ROBOT USING CONTROL SYSTEM - HAJI AHMAD, FAIZAL (Universiti Teknologi Petronas, 2004)
This project presents a Single Wheel Balancing Robot. Basically, the main idea of the project is to balance a structure on a wheel using motor. The wheel will balance the structure forward and backward, trying to make the structure not to fall. This project will involve with a precise weight distributed fabricated structure and a very fast control systems controlling the motor thus the robot itself. The objective of the project is to balance the robot structure using control system methods, which is simulated using the MATLAB software and interface with the robot using Quanser systems. The objective also consists of solving the control problems using control systems theory such as Root Locus and Proportional-Integral-Differential, proving the effectiveness of the theory in fast response control systems. The student's main mission of the project is to fabricate a good robot structure with a very stable center of gravity, study the basic and various type of controller techniques, studythe robot components (motor, encoderand etc), study and experiment the Quanser interface module, interface the fabricated robot structure with MATLAB using Quanser systems, and proceed with balancing the structure. Thesecond mission is to test the complete system with studied control systems and control troubleshooting. Lastly a technical paper will be produced regarding the results of the real simulation.